Financial transition in Europe and Central Asia : challenges of the new decade - Fleming, Alexander; Bokros, Lajos; Votava, Cari (Washington, D.C. : World Bank, 2001)
The financial sectors of the post-communist economies of Europe and Central Asia are perhaps where the most intractable problems existed and where the most difficult reforms where forced to begin. This book brings together the views of a wide range of financial sector experts, and shares some of the lessons learned from the past decade. With the benefit of hindsight, it also looks toward the second decade of financial transition.
Based on two seminars and a conference in respectively Prague and Benesov in the Czech Republic at the time of the World Bank-International Monetary Fund annual meetings in Sept. 2000.
Includes bibliographical references.
usc 6/6/17
Loans
Keywords: Finance; Finance; Banks and banking; Banks and banking